Improved Resistance to Stress-Corrosion-Cracking Failures via Optimized Retrogression and Reaging of 7075-T6 Aluminum Sheets - Baydogan, Murat; Cimenoglu, Huseyin; Sabri Kayali, E.; Rasty, Jahan (Springer Science and Business Media LLC, 2008)
The effect of retrogression and reaging (RRA) treatment on the hardness and stress corrosion cracking (SCC) susceptibility of 7075 aluminum alloy sheets was systematically investigated. The material in its as-received T6-temper state was retrogressed at 170 °C, 220 °C, 240 °C, and 380 °C for different durations between 15 seconds and 60 minutes. Subsequent reaging was performed at the T6 aging condition (120 °C for 24 hours). RRA-treated alloys exhibited a better combination of hardness and SCC resistance than the T6-temper state when retrogressed between 170 °C and 240 °C for short durations. However, a retrogression temperature of 380 °C resulted in considerable reduction in both hardness and SCC resistance. Among retrogression temperatures employed, 170 °C provided an optimum combination of hardness and SCC resistance, corresponding to 20 pct improvement in hardness and 85 pct improvement in SCC resistance. In this article, improvements in hardness and SCC resistance of 7075 alloy upon RRA treatment are discussed.